Architecture, composition and placement of nests of the Cipo Canastero Asthenes luizae (Aves: Furnariidae), a bird endemic to Brazilian mountaintops. Issue 7 (24th February 2019) - Costa, Lilian Mariana; Freitas, Guilherme Henrique Silva de; Rodrigues, Marcos
ABSTRACT: Cipo Canastero ( Asthenes luizae ) is a bird endemic to Brazilian mountaintops, inhabiting rock outcrop habitats of the campos rupestres in the southern Espinhaço Range. Available data about Cipo Canastero's breeding biology are scarce, incomplete or inconsistent. All nests found to date were built in the plant Vellozia nivea . Based on 84 nests found from 2009 to 2017 in four sites at Serra do Cipó, we described in detail their nesting habits focusing on three groups of characters: nest architecture, composition, and placement. Also, we described nest building. Our major new findings on the nesting habits of A. luizae were: three nest layers distinguishable, inner lining covering the entire nest interior, tunnels and tubes are absent, and the nest sites are not restricted to V. nivea . We recorded a wide range of nest sites, from ground, grasses and rupicolous bromeliads to shrubs and trees, including at least 30 supporting-plant species. Nest supports varied among study sites. Nest building lasted 22 days (one nest) and was done by both members of the pair. Our data can be useful for species conservation and contribute to the knowledge of the natural history of the genus Asthenes.